2017
DOI: 10.1016/j.jpeds.2017.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Treatment Effects on Motor Function, Cognition, and Behavior in Boys with Klinefelter Syndrome

Abstract: ClinicalTrials.gov: NCT00348946.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
56
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 58 publications
6
56
1
Order By: Relevance
“…Although the incidence of sex chromosome aneuploidies (SCAs) is estimated to be one in every 500 live births, between 75% and 90% of cases remain undiagnosed in their lifetime . Children with these disorders present with dysfunction in speech, language, and motor development . The phenotype spans a wide range of associated symptoms that vary in severity depending on the specific SCA, timing of diagnosis, and family history …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the incidence of sex chromosome aneuploidies (SCAs) is estimated to be one in every 500 live births, between 75% and 90% of cases remain undiagnosed in their lifetime . Children with these disorders present with dysfunction in speech, language, and motor development . The phenotype spans a wide range of associated symptoms that vary in severity depending on the specific SCA, timing of diagnosis, and family history …”
Section: Introductionmentioning
confidence: 99%
“…Over 50 years of publications have demonstrated significant evidence to the importance of early identification of SCAs and the positive impact of early intervention on neurodevelopmental outcomes . These studies have also shown that children prenatally diagnosed with an SCA have less neurodevelopmental dysfunction, fewer behavioral disturbances, and IQs within or above the normal limits.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations